Increase in DNA methylation in patients with amyotrophic lateral sclerosis carriers of not fully penetrant SOD1 mutations. Issue 1 (2nd January 2018) - Coppedè, Fabio; Stoccoro, Andrea; Mosca, Lorena; Gallo, Roberta; Tarlarini, Claudia; Lunetta, Christian; Marocchi, Alessandro; Migliore, Lucia; Penco, Silvana
Abstract: Objective : More than 180 different superoxide dismutase 1 (SOD1) mutations have been described to date in amyotrophic lateral sclerosis (ALS) patients, including not completely penetrant ones leading to phenotypic heterogeneity among carriers. We collected DNA samples from five ALS families with not fully penetrant SOD1 mutations (p.Asn65Ser, p.Gly72Ser, p.Gly93Asp, and p.Gly130_Glu133del) searching for epigenetic differences among ALS patients, asymptomatic/paucisymptomatic carriers and non-carrier family members. Methods : Global DNA methylation levels (5-methylcytosine levels) were determined in blood DNA samples with an enzyme-linked immunosorbent assay (ELISA), and the methylation analysis of SOD1, FUS, TARDBP and C9orf72 genes was performed using Methylation-Sensitive High-Resolution Melting (MS-HRM) technique. Results : Global DNA methylation levels were significantly higher in blood DNA of ALS patients than in asymptomatic/paucisymptomatic carriers or family members non-carriers of SOD1 mutations, and a positive correlation between global DNA methylation levels and disease duration (months) was observed. SOD1, FUS, TARDBP and C9orf72 gene promoters were demethylated in all subjects. Conclusions : The present study suggests that global changes in DNA methylation might contribute to the ALS phenotype in carriers of not fully penetrant SOD1 mutations, thus reinforcing the role of epigenetic factors in modulating the phenotypic expression of the disease.